Gold(I)-catalysed synthesis of a furan analogue of thiamine pyrophosphate - Iqbal, Amjid; Sahraoui, El-Habib; Leeper, Finian J. (Beilstein Journal of Organic Chemistry, 2014)
An analogue of thiamine having a furan ring in place of the thiazolium ring has been synthesised by a short and efficient route, involving gold(I)-catalysed cyclisation of an alkynyl alcohol to form the furan ring. The furan analogue of thiamine diphosphate (ThDP) was also made and tested for binding to and inhibition of pyruvate decarboxylase (PDC) from Zymomonas mobilis (overexpressed in E. coli with a N-terminal His-tag). It is a very strong inhibitor, with a Ki value of 32.5 pM. It was also shown that the furan analogue of thiamine can be functionalised at the C-2 position, which will allow access to mimics of reaction intermediates of various ThDP-dependent enzymes.
Keywords: furan synthesis; gold-catalysed cyclisation; pyruvate decarboxylase; thiamine diphosphate